Frequency, distribution, and risk factors of oral mucosal lesions in a Colombian population: cross-sectional study - Toro-Alzate, Maricela; Saldarriaga-Saldarriaga, Andrés; Sánchez-Muñoz, Lina Beatriz; Rodríguez-Montoya, Gloria Patricia; Posada-López, Adriana; Álvarez-Gómez, Gloria Jeanethe (Revista Facultad de Odontología Universidad de Antioquia, 2024)
Introduction: oral mucosa lesions (OML) are any abnormal variations in appearance, color, texture, swelling, or loss of integrity of the oral mucosa. The worldwide prevalence varies from 4.9 % to 64.7 %. This study aimed to determine the frequency of oral lesions in patients who consult the Facultad de Odontología, Universidad de Antioquia, Medellín, Colombia. Methodology: a cross-sectional study was carried out using a structured instrument with sociodemographic, clinical, and habit variables and systematic clinical examination according to the WHO. Statistical analysis was univariate and bivariate, calculating the average and standard deviation for the age variable and absolute and relative frequencies for each sociodemographic and clinical variable. Chi-square tests were done for differences in proportions. Results: 539 patients, the average age was 35.2 years (SD=23.5 years). The frequency of patients with oral lesions was 75.9 % (409). Statistically significant differences were found between the number of lesions and age, use, and type of appliances. Orthodontic appliances were the most common cause of injury (43.1 %). The most frequent lesions were traumatic (68.2 %), followed by vascular (22 %), exfoliative cheilitis (20 %), infectious (17.1 %), and reactive (5.13 %). Conclusions: the prevalence of OML in this population is high, with women mainly affected. The study highlights the importance of making a systematic clinical examination and correlating the findings with the patient's history to establish a diagnosis, prognosis, and appropriate treatment.